Use of Metallic Nanoparticles Synthesized from Plant Extracts in Wound Healing—A Review - Anaís Bezerra de Gusmão; Priscilla Barbosa Sales de Albuquerque; Ana Carolina de Carvalho Correia (Applied Nano)
Wound healing is rarely seen as a problem in healthy individuals; however, under certain pathophysiological conditions, this process can be impaired, leading to the emergence of chronic wounds, which are themselves a serious public health problem. This work aimed to review the most important recent literature on the use of nanoparticles of Ag, Au, and Zn produced from plant extracts and their application as healing agents. To that end, we provide an insight into the pathophysiology of wound healing and the main routes to obtaining metallic nanoparticles. The methodology of synthesis, which is part of the so-called green synthesis, has been the focus of several studies on the use of medicinal plants as a substrate to produce silver, gold, and zinc nanoparticles. Their use as wound healing agents is closely related to their natural antimicrobial, anti-inflammatory, and cicatrizing properties. Finally, we address in vitro and in vivo studies on the efficiency of metallic nanoparticles (MNPs) synthesized from plant extracts and applied to wound healing in different pharmaceutical forms. For instance, the excellent wound contraction rates obtained from silver and gold NPs, respectively, were obtained from Euphorbia milii (92%) and Plectranthus aliciae (almost 97%) extracts in in vivo and in vitro analyses. Based on the satisfactory results, we find that MNPs are a potential therapeutic alternative compared to traditional synthetic healing agents and foresee the production of new pharmaceutical drugs.